Targeting emerging amino acid dependencies and transporters in cancer therapy - Akinlalu, Alfred; Ogberefor, Emmanuel; Gao, Tommy; Sun, Dali (Frontiers in Pharmacology, 2025)
Amino acid metabolism is an important vulnerability in cancer. Established strategies such as arginine depletion, glutaminase inhibition, tryptophan-kynurenine modulation, and methionine restriction have shown that these pathways can be targeted in patients. At the same time, clinical trials reveal two consistent challenges: tumors can adapt by redirecting their metabolism, and reliable biomarkers are needed to identify patients who are most likely to benefit. Recent studies point to additional amino acids with translational potential. In pancreatic cancer, histidine and isoleucine supplementation has been shown in preclinical models to be selectively cytotoxic to tumor cells while sparing normal counterparts. In glioblastoma, threonine codon-biased protein synthesis programs that support growth; in other contexts, lysine breakdown suppresses interferon signaling through changes in chromatin structure; and alanine released from stromal cells sustains mitochondrial metabolism and therapy resistance. These dependencies are closely tied to amino acid transporters, which act as both nutrient entry points and measurable biomarkers. In this review, we summarize current evidence on histidine, isoleucine, threonine, lysine, and alanine as emerging metabolic targets, and discuss opportunities and challenges for clinical translation, with emphasis on transporter biology, biomarker development, and therapeutic combinations.